Characteristics and accumulation period of Cambrian-Ordovician hydrocarbon inclusions in Yingmai 7 area, Tabei Uplift. Issue 1 (November 2020) - Fan, Shan; Zhang, Huifang; Lou, Hong; Shi, Chaoqun; Zhou, Siyu; Wang, Zuotao; Ma, Xiaodan; Jiang, Jun
Abstract: According to the fluorescence characteristics of hydrocarbon inclusions under the microscope, the interpenetration relationship with the occurrence veins, and the homogenization temperature, the hydrocarbon inclusions developed in the Cambrian-Ordovician reservoir in Yingmian 7 area can be divided into four periods, which correspond to four hydrocarbon accumulation events respectively. The periods of accumulation determined by the analysis of homogenization temperature and burial history are as follows: late Caledonian to early Hercyian low mature heavy oil filling, late Hercyian medium mature normal oil filling, early Himalayan high mature light oil filling and late Himalayan over mature natural gas filling. Among them, periods of I, II hydrocarbon inclusions distribution range is limited, only visible in part of the wells in Yingmai 7 area; periods of III, IV hydrocarbon inclusions in Yingmai 7 area are widely distributed, which reveals the Himalayan period of the two-stage oil and gas filling on the reservoir formation.